2020
DOI: 10.3389/fcell.2020.00117
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Feedback Loop of Hippo- and c-Jun-Amino-Terminal Kinase Signaling Pathways Regulates Amyloid-Beta-Mediated Neurodegeneration

Abstract: Alzheimer's disease (AD, OMIM: 104300) is an age-related disorder that affects millions of people. One of the underlying causes of AD is generation of hydrophobic amyloid-beta 42 (Aβ42) peptides that accumulate to form amyloid plaques. These plaques induce oxidative stress and aberrant signaling, which result in the death of neurons and other pathologies linked to neurodegeneration. We have developed a Drosophila eye model of AD by targeted misexpression of human Aβ42 in the differentiating retinal neurons, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 106 publications
(170 reference statements)
0
38
0
Order By: Relevance
“…Previous research in flies and humans has implicated activation of the highly conserved JNK signaling pathway in AD ( Irwin et al., 2020 ; Sarkar et al., 2018 ; Tare et al., 2011 ; Wang et al., 2014 ; Yarza et al., 2015 ). Phosphorylation of JNK transcriptionally activates apoptosis, and increased levels of pJNK have been reported in patients with AD ( Wang et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research in flies and humans has implicated activation of the highly conserved JNK signaling pathway in AD ( Irwin et al., 2020 ; Sarkar et al., 2018 ; Tare et al., 2011 ; Wang et al., 2014 ; Yarza et al., 2015 ). Phosphorylation of JNK transcriptionally activates apoptosis, and increased levels of pJNK have been reported in patients with AD ( Wang et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…In humans and AD models, Aβ42 accumulation is linked to increases in activation of the JNK pathway ( Irwin et al., 2020 ; Ray et al., 2017 ; Sarkar et al., 2018 ; Tare et al., 2011 ; Wang et al., 2014 ; Yarza et al., 2015 ). The JNK signaling pathway, part of the mitogen-activated protein kinase (MAPK) superfamily, is highly conserved and transcriptionally activates apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult eye images were captured after freezing flies at − 20 °C for ~ 4 h. Images were taken on a MrC5 color camera mounted on an Axioimager.Z1 Zeiss Apotome using a Z-sectioning function of Axiovision software 4.6.3 71 . The final images were prepared using Adobe Photoshop CS6 software.…”
Section: Methodsmentioning
confidence: 99%
“…In Drosophila, researchers expressed high levels of human Aβ42 polypeptide in the differentiating photoreceptor neurons and developed a transgenic model system in Drosophila eye [111]. A Chinese traditional medicinal prescription called KSOP1009 could strongly suppress Aβ42-induced eye degeneration and the locomotive dysfunctions via suppression of the hyperactivation of JNK activity and apoptosis [112]. A recent study found a positive feedback loop of Hippo and JNK signaling which regulates Aβ mediated neurodegeneration.…”
Section: Jnk Inhibitorsmentioning
confidence: 99%